Prevalence of foliar blight pathogens attacking wheat in Shivalik foothills and significance of sowing dates for its management - and V.S. VERMA, DINESH SINGH*, MAHINDER SINGH (Indian Phytopathology, 2007)
Prevalence and distribution of wheat foliar blight pathogens in Shivalik foothill region of Jammu and Kashmir (India) and effect of sowing dates on disease severity were analyzed for four rabi seasons from 2001-02 to 2004-05. Helminthosporium sativum, Alternaria triticina, H. spicifer and Pyrenophora triticirepentis were isolated with an average frequency of 66.87, 23.65, 3.97 and 3.50 per cent, respectively and highest frequency of isolation was 72 (Rajouri), 26.5 (Jourian, Doda and Bhaderwah), 5.5 (Akhnoor) and 4.5 (Kathua and Katra), respectively. Setosphaeria halodes and Helminthosporium bico/or were occasionally found associated. Early sowing (October, 25) was found to be significantly most effective in reducing the disease severity which was 3.66, 3.66, 3.66 and 2.33 per cent with variety PBW 175 and November, 14 sowing recorded the maximum grain yields of 21.67, 22.05, 21.70 and 22.90 qhaÂ·1 having disease severity of 16.66, 18.33, 21.66 and 18.33 per cent with the variety PBW 299 in the crop season 2001-02, 2002-03, 2003-04, 2004- 05, respectively. Meteorological parameters significantly influenced the grain yield and disease incidence. The maximum pooled grain yields of 22.08, 20.01, 21.37, 22.10, and 18.98 qha' were recorded on November ,14 sown crop where meteorological parameters were optimum for the whole crop season and minimum pooled disease severity of 11.66, 12.49, 3.32, 5.91 and 24.58 was recorded on October, 25 sown crop where environmental condition for the growth of crop was optimum according to its different stages but unfavorable for the pathogen during the susceptible stage (60 days old crop) of the crop with the variety PBW 299, RSP 303, PBW 175, Raj 3077 and HD 2838, respectively.